Preparation and Study of nticancer Activity of Curcuminoid-Rich Curcuma longa Extracts (CRE) and CRE-Cyclodextrin Inclusion Complexes - Likit Lateh (2019)
Thesis (Ph.D.(Pharmaceutical Sciences))--Prince of Songkla University, 2018